Faktor-Faktor Yang Berhubungan Dengan Proses Penyembuhan Luka Post SC Di Rumah Sakit Permata Medika Kota Semarang - Dian Kurnia; Widya Mariyana; Mudy Oktiningrum (Vitamin : Jurnal ilmu Kesehatan Umum, 2024)
The maternal mortality rate of post-SC infection reaches 7.3%, and 90% causes postpartum morbidity. This study aimed to determine the factors associated with the SC wound healing process. This study used a quantitative method, a type of analytic survey research with a cross-sectional design approach. The population of this study were all post-SC mothers in the postpartum ward of Permata Medika Hospital. The sampling technique used was a consecutive sampling of 34 respondents. The research instrument was a questionnaire. Data analysis was done using univariate and bivariate (chi-square test, alpha = 0.05). The results of this study showed that there was a relationship between the SC wound healing process and early mobilisation (p-value 0.000 < 0.05), which means there was a relationship between the SC wound healing process and nutritional status (BMI) (p-value 0.04 < 0.05), and there was a relationship between the SC wound healing process and anaemia (p-value = 0.00 <0.05) because if p-value < 0.05, then Ha is accepted. Ho is rejected, meaning a significant relationship exists between early mobilisation, nutritional status, and anaemia in SC wound healing. Many factors affect the SC wound healing process, three of which are early mobilisation factors, which, if done before 6–8 hours after SC, has more potential to accelerate SC wound healing; normal nutritional status as an expression of a person's nutritional balance, which plays a role in the process of body tissue growth and has an impact on the duration of wound healing; and anaemia, which anaemia is a symptom of low haemoglobin levels in the blood and obstructs oxygen flow and prevents the growth and repair of tissue from the SC surgical incision.